A fast method for the determination of 210Pb by LSC in liquid samples - Camilla da Silva Sampaio Lucena; Wanderson de Oliveira Sousa; Bernardo Maranhão Dantas (Brazilian Journal of Radiation Sciences, 2019)
210Pb is a naturally occurring radionuclide, widely distributed on the earth´s surface and can be incorporated by humans through food chain or directly by ingestion or inhalation in situations of occupational or accidental exposures. It concentrates in bone tissue when absorbed, presenting a rather long biological half-life and producing one of the highest skeletal doses among naturally occurring radionuclides under conditions of average background exposure. Because of its metabolic and dosimetric characteristics, 210Pb becomes an important isotope from the radiation protection point of view. This work presents the development of a methodology for the determination of 210Pb by liquid scintillation. It is the modification of a sequential analysis for naturally occurring radionuclides in environmental samples without the need of waiting for secular equilibrium to be achieved with 210Bi. The methodology has shown to be precise, stable and provides consistent results when evaluated according to the criteria established in the Brazilian Intercomparison Program promoted by the IRD.